Theoretical and experimental analysis of inductor characteristics for hearing implants - Asadour, Christian; Safi, Abdulrahman (My University, 2026)
Implantable hearing devices rely on inductive coils to transfer power and signals wirelessly across the skin. The electrical and magnetic properties of these coils directly affect device effi-ciency, and size. This thesis investigates how core material, core diameter, wire diameter, and number of turns affect the inductance, DC resistance, quality factor, magnetic flux, and physical size of wire-wound inductors intended for hearing implant applications. The work was carried out in collaboration with Oticon Medical. A MATLAB model was implemented and evaluated for five core materials across seven core di-ameters and two wire diameters at a target inductance of 100 μH. Four prototype coils were also hand-wound on ferrite rod cores at Oticon Medical's laboratory and measured using a Source-tronic ST2827A precision LCR meter. The theoretical results were compared with the experi-mental measurements to evaluate how well the model reflected practical coil behavior. The findings provide a comparative framework for understanding how material and geometric choices affect coil performance and highlight key considerations for future coil design in im-plantable hearing devices.